2018
DOI: 10.1111/lam.13062
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of antagonism, modulation of cytokines and extracellular matrix proteins by Bifidobacterium strains

Abstract: The skin is the first line of defence against invasive micro-organisms, and its local microbiota provides additional protective functions based on antagonism against pathogenic micro-organisms and immunomodulation. Based on in vitro assays using Bifidobacterium spp. we demonstrated the antagonistic potential, as well as capacity in stimulating the production of cytokines and proteins of the extracellular matrix that these bacteria may exert on skin cells. This positive influence suggests the use of a consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a result, recent research efforts have tended to focus on the immunomodulatory effects of postbiotics. Furthermore, the use of non-viable microbial cell extracts to treat wounds has shown that inactivated postbiotic bifidobacteria are more effective than viable forms in some subjects [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, recent research efforts have tended to focus on the immunomodulatory effects of postbiotics. Furthermore, the use of non-viable microbial cell extracts to treat wounds has shown that inactivated postbiotic bifidobacteria are more effective than viable forms in some subjects [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the levels of IL-8 decreased in all inactivated bacteria and live B. longum and B. pseudolongum , and the decrease was greater in the inactivated bacteria. In the case of IL-6, an anti-inflammatory cytokine, all tested inactivated and live bifidobacteria reduced its levels, with the exception of live B. pseudolongum 119 1A [ 33 ].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%